Ethnic Mobility and the Formation of Political Identity in Indonesia - Refly Setiawan; Sergey A. Sergeev (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
Indonesia is an archipelagic country that has many tribes and cultures, which make Indonesia a multi-cultural country. There are 5 religions recognized in Indonesia based on the Law of the Republic of Indonesia, namely: Islam, Christianity, Hinduism, Buddhism, and Confucianism. This research is related to ethnic mobility and the formation of political identity in Indonesia which is currently very interesting to be discussed by various researchers around the world, not only in Indonesia. In this study, researcher discuss ethnic mobility and the formation of political identity based on history that has occurred in Indonesia to date. The Indonesian nation Indonesia adheres to the Pancasila ideology so that the national ideology has a major influence on the unity and integrity of the nation. In this study, researcher also examined the ideological values of Pancasila and the nation's unifying motto called Bhinneka Tunggal Ika. This study uses a qualitative descriptive approach in which the researcher conducts a descriptive elaboration of ethnic mobility and the formation of political identity in Indonesia and ethnic participation in political parties in Indonesia. The results of the study show that in the past there were still many Indonesian people who considered themselves local residents and were reluctant to accept other ethnic groups to occupy certain positions in an area, including political positions. The separatist movement that emerged in an area due to the inequality of one region with another, such as the islands of Java and Sumatra, had caused inter-ethnic conflict and many people were anti-Chinese in the 90s. However, currently, Indonesia has provided space for various tribes and religions to be involved in political development in Indonesia based on Pancasila and the 1945 Constitution. Indonesia as a multiethnic country has upheld democratic freedoms for all nations and provided regional autonomy policies for each region in order to improve public welfare.